In-mold molded article and method for manufacturing the same

JP2026165646APending Publication Date: 2026-10-14FP CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025058134
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0014】 本発明のインモールド成形品は、厚み60μm以上の透明な二軸延伸ポリオレフィンシート(1a)を含む透明基材シート層(1A)と、透明基材シート層(1A)と一体化され、廃プラスチックの表面塗膜に由来する塗膜片を含む再生プラスチック(2a)を含有する樹脂材料からなる射出成形樹脂層(2)とを有する。このため、本発明のインモールド成形品は、再生プラスチック(2a)を使用してインモールド成形法により製造でき、十分な機械的強度を有し、しかも意匠性の良好なものである。 また、本発明のインモールド成形品の製造方法によれば、十分な機械的強度を有し、しかも意匠性の良好なインモールド成形品を製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165646000001_ABST
    Figure 2026165646000001_ABST
Patent Text Reader

Abstract

This invention provides in-mold molded products that can be manufactured using recycled plastic, possess sufficient mechanical strength, and have a good aesthetic appearance. [Solution] The in-mold molded product (3) comprises a transparent base material sheet layer (1A) containing a transparent biaxially oriented polyolefin sheet with a thickness of 60 μm or more, and an injection-molded resin layer (2) made of a resin material containing recycled plastic, including coating fragments derived from the surface coating of waste plastic, which is integrated with the transparent base material sheet layer (1A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an in-mold molded article and a method for producing the in-mold molded article.

Background Art

[0002] In recent years, from the perspectives of global environmental issues, resource depletion issues and the like, the importance of recycling plastic materials has been increasing more and more. For example, in Europe, a draft European End-of-Life Vehicle (ELV) Directive has been proposed, which requires that 25% or more of the plastic materials used in the production of new vehicles be recycled plastics, and 25% of the recycled plastics be derived from end-of-life vehicles, and movements toward improving the recycling rate are accelerating. In response to such trends, techniques for using recycled plastics derived from end-of-life vehicles as materials for newly manufactured vehicles are being studied.

[0003] When horizontal material recycling, in which the same component is produced using a recycled material obtained by regenerating a discarded component, is carried out for automobile bumpers, there have been the following two problems. One is that the mechanical strength of the bumper material itself produced using the recycled material is lower than that of the waste bumper. The other is that it is difficult to completely remove coating film fragments derived from the surface coating film of the waste bumper from the recycled material.

[0004] Accordingly, studies are underway to enhance the design properties of bumpers while actively emphasizing that the material is a recycled material, by not actively removing the surface coating film of the waste bumper from the recycled material, but rather allowing coating film fragments to remain. That is, by making the coating film fragments contained in the bumper produced using the recycled material stand out, a stardust-like pattern is made to appear on the surface to attempt to improve the aesthetic appearance. However, for example, when a molded article is produced by injection molding a recycled material containing coating film fragments, the coating film fragments rarely appear on the surface of the molded article, and it has not been possible to produce a molded article that can sufficiently demonstrate that it is made of a recycled material.

[0005] Furthermore, injection-molded parts manufactured using recycled materials exhibit reduced mechanical strength compared to those manufactured using virgin materials. One possible solution to this problem is to utilize in-mold molding technology. As an in-mold molding technique, a technique using biaxially oriented polypropylene film as an in-mold label film is known (see, for example, Patent Document 1). Patent Document 1 describes a highly rigid biaxially oriented polypropylene film for use as an in-mold label film.

[0006] However, the biaxially oriented polypropylene film described in Example 1 of Patent Document 1 is a thin film with a thickness of 20 μm. While it contributes to improving the strength of small components such as containers, it does not contribute to improving the strength when used in molded products that require high strength, such as automobile bumpers. [Prior art documents] [Patent Documents]

[0007] [Patent Document 1] Patent No. 6414378 [Overview of the project] [Problems that the invention aims to solve]

[0008] The problem that this invention aims to solve is to provide an in-mold molded product that can be manufactured using recycled plastic, has sufficient mechanical strength, and also has good design aesthetics. Furthermore, the present invention aims to provide a method for manufacturing in-mold molded articles that can produce in-mold molded articles having sufficient mechanical strength and good design aesthetics. [Means for solving the problem]

[0009] To solve the above problems, the following means are provided.

[0010] (1) A transparent substrate sheet layer (1A) including a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more, An in-mold molded product comprising an injection-molded resin layer (2) made of a resin material that is integrated with the transparent substrate sheet layer (1A) and contains recycled plastic (2a) including coating fragments derived from the surface coating of waste plastic.

[0011] (2) The in-mold molded product according to (1), wherein the transparent substrate sheet layer (1A) has a crystallinity of 70% or more due to X-ray diffraction when X-rays are irradiated from the cut surface. (3) The in-mold molded product according to (1), wherein, by observing a rectangular area measuring 10 mm vertically and 10 mm horizontally on the surface of the transparent substrate sheet layer (1A) opposite to the injection-molded resin layer (2) with a microscope at 20x magnification, 50 to 80 of the coating fragments, each with a maximum length of 0.25 mm or less, can be identified.

[0012] (4) A method for manufacturing an in-mold molded product that produces an in-mold molded product as described in any of (1) to (3), A sheet installation process in which a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more is placed inside the cavity of the mold, The process includes a molding step of injecting and molding a resin material containing recycled plastic (2a) which includes coating fragments derived from the surface coating of waste plastic into the cavity, A method for manufacturing an in-mold molded product, comprising the molding step of injecting the resin material into the cavity so that it flows in a direction along the sheet surface of the biaxially oriented polyolefin sheet (1a).

[0013] (5) The method for producing an in-mold molded article according to (4), wherein the biaxially oriented polyolefin sheet (1a) has a degree of crystallinity of 70% or more due to X-ray diffraction when irradiated with X-rays from the cut surface. [Effects of the Invention]

[0014] The in-mold molded article of the present invention has a transparent base material sheet layer (1A) including a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more, and an injection molded resin layer (2) made of a resin material integrated with the transparent base material sheet layer (1A) and containing recycled plastic (2a) that includes coating film fragments derived from surface coating films of waste plastic. For this reason, the in-mold molded article of the present invention can be manufactured by the in-mold molding method using the recycled plastic (2a), has sufficient mechanical strength, and also has good design properties. Furthermore, according to the method for manufacturing an in-mold molded article of the present invention, an in-mold molded article that has sufficient mechanical strength and also has good design properties can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] [Figure 1] Figure 1 is a schematic cross-sectional view for describing an example of the in-mold molded article according to the present embodiment. [Figure 2] Figure 2 is a schematic process diagram for describing the manufacturing method of the in-mold molded article shown in Figure 1. [Figure 3] Figure 3 is a schematic process diagram for describing the manufacturing method of the in-mold molded article shown in Figure 1. [Figure 4] Figure 4 is a photograph of the surface on the base material sheet layer side of the molded article in Example 3. [Figure 5] Figure 5 is a photograph of the surface on one side of the molded article in Comparative Example 2. [Figure 6] Figure 6 shows the microscope observation results of the central portion 1 in the molded articles of Example 3 and Comparative Example 2. [Figure 7] Figure 7 shows the microscope observation results of the central portion 2 in the molded articles of Example 3 and Comparative Example 2. [Figure 8] Figure 8 shows the microscope observation results of the side portion 1 in the molded articles of Example 3 and Comparative Example 2. [Figure 9] Figure 9 shows the microscope observation results of the side portion 2 in the molded articles of Example 3 and Comparative Example 2. [Figure 10]FIG. 10(a) is an SEM photograph of a cross section of the molded article of Example 3. FIG. 10(b) is a photograph of a large-area coating film fragment visually recognized on the surface of the molded article of Example 3. [Figure 11] FIG. 11(a) is an SEM photograph of a cross section of Comparative Example 2. FIG. 11(b) is a photograph of a large-area coating film fragment visually recognized on the surface of the molded article of Comparative Example 2. [Figure 12] FIG. 12 is a drawing showing the observation positions with a microscope on the molded articles of Example 3 and Comparative Example 2. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0016] In order to solve the above problems and realize a molded article that has sufficient mechanical strength and excellent design properties, the present inventors conducted intensive studies focusing on the design properties of molded articles containing coating film fragments derived from the surface coating film of waste plastic. Specifically, the present inventors conceived that the coating film fragments derived from the surface coating film of waste plastic contained in molded articles manufactured using recycled plastic should not be regarded as unnecessary elements that degrade the appearance, but instead be actively utilized as a material that demonstrates the appeal of products made from recycled plastic and enhances design properties.

[0017] Then, the present inventors did not attempt to manufacture recycled plastic free of coating film fragments derived from the surface coating film of waste plastic by removing the coating film adhering to the surface of waste plastic, but instead conceived of making the coating film fragments contained in the recycled plastic stand out to develop a pattern on the surface of the molded article.

[0018] However, when surface-coated waste plastic is used without removing the coating film to obtain recycled plastic (2a), and this is directly subjected to injection molding, sufficient coating film fragments cannot be made to appear on the surface of the obtained molded article. In addition, the method of injection molding the above recycled plastic (2a) failed to obtain a molded article having sufficient mechanical strength.

[0019] Therefore, the inventor focused on the in-mold molding method and manufactured a molded product using the recycled plastic (2a) described above. By forming a molded product in which a resin layer made of recycled plastic (2a) and a base sheet layer are integrated using the in-mold molding method, a molded product with better mechanical strength can be obtained compared to a molded product manufactured using the injection molding method.

[0020] Furthermore, in order to improve the aesthetic appeal of molded products by making the coating fragments derived from the surface coating of waste plastics more conspicuous, the inventors diligently conducted research to increase the area of ​​coating fragments appearing on the surface of the base sheet layer (1A) of the in-mold molded product, as shown below.

[0021] In other words, the coating fragments derived from the surface coating of waste plastic are formed by crushing the waste plastic and have various sizes and shapes, such as plate-like, rod-like, and columnar. Therefore, the area of ​​coating fragments that can be recognized from the surface of the base sheet layer (1A) of the in-mold molded product varies greatly depending on the orientation of the coating fragments within the in-mold molded product.

[0022] The inventors have conducted thorough research and found that when injecting the above-mentioned recycled plastic (2a) into the cavity of a mold using an in-mold molding method, the recycled plastic (2a) should be injected in a direction that flows along the sheet surface of the sheet that will become the base sheet layer (1A). In other words, they found that by injecting the above-mentioned recycled plastic (2a) into the cavity using the above method, the orientation of the coating fragments contained in the recycled plastic (2a) is aligned such that the area of ​​coating fragments visible from the surface of the base sheet layer (1A) is greater than the area of ​​coating fragments appearing in the cross-sectional direction of the base sheet layer (1A).

[0023] This is presumed to be due to the following mechanism. Specifically, the recycled plastic (2a) injected into the mold cavity by the above method and in contact with the sheet placed in the cavity flows along the sheet surface of the base sheet layer (1A) while maintaining its fluid state. At this time, the coating fragments contained in the recycled plastic (2a) move together with the resin contained in the recycled plastic (2a) while being aligned in a direction that offers less resistance to the flow direction. As a result, the coating fragments are oriented such that the area of ​​the coating fragments visible from the surface on the base sheet layer (1A) side is greater than the area of ​​the coating fragments appearing in the cross-sectional direction of the base sheet layer (1A).

[0024] In contrast, if no sheet is placed in the mold cavity, the recycled plastic (2a) injected into the mold cavity comes into contact with the mold immediately after injection and is rapidly cooled. As a result, the fluidity of the recycled plastic (2a) rapidly decreases, making it difficult for the coating fragments contained in the recycled plastic (2a) to move together with the resin contained in the recycled plastic (2a). Therefore, the coating fragments are fixed without being aligned in a direction that offers less resistance to the flow direction of the recycled plastic (2a). From this, it is estimated that if no sheet is placed in the mold cavity, the area of ​​coating fragments visible from the surface will be smaller compared to when the sheet is placed in the mold cavity.

[0025] In in-mold molded products into which recycled plastic (2a) is injected using the method described above, the orientation of the coating fragments is aligned as described above. As a result, the surface on the base sheet layer (1A) side shows the presence of coating fragments much more conspicuously compared to the surface of molded products manufactured using injection molding. Consequently, in the above-described in-mold molded product, the number of coating fragments visible from the surface on the base sheet layer (1A) side increases, and the area of ​​each coating fragment visible from the surface on the base sheet layer (1A) side also increases, forming an aesthetically pleasing stardust-like pattern consisting of coating fragments on the surface on the base sheet layer (1A) side.

[0026] However, when using a commonly used film as the film placed in the mold cavity before injecting the recycled plastic (2a), in-mold molded products in which recycled plastic (2a) was injected using the method described above did not yield molded products with sufficient mechanical strength. Therefore, in order to improve the mechanical strength of molded products, the inventor focused on the film placed inside the mold cavity in the in-mold molding method and conducted extensive research.

[0027] As a result, it was found that a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more should be placed inside the mold cavity before injecting the recycled plastic. The biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more exhibits excellent rigidity and impact strength, resulting in good mechanical strength due to the synergistic effect of being biaxially oriented and having a sufficient thickness of 60 μm or more.

[0028] Therefore, by injecting the recycled plastic (2a) into the cavity of a mold in which a biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more is installed, an injection-molded resin layer made of recycled plastic (2a) and a base sheet layer (1A) made of a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more are integrated, resulting in a molded product with sufficient mechanical strength.

[0029] Furthermore, the inventors of the present invention have come to the conclusion that by placing a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more in the cavity of a mold, injecting a resin material containing recycled plastic (2a) including coating fragments derived from the surface coating of waste plastic into the cavity, and injecting the resin material into the cavity so as to flow in a direction along the sheet surface of the biaxially oriented polyolefin sheet (1a), it is possible to form an in-mold molded product that has sufficient mechanical strength and good design properties.

[0030] The in-mold molded product and the method for manufacturing the in-mold molded product according to this embodiment will be described in detail below, with appropriate reference to the drawings. In the drawings used in the following description, characteristic parts may be enlarged for convenience in order to make the features of the present invention easier to understand. Therefore, the dimensional ratios of each component may differ from those in reality. The materials, dimensions, etc. exemplified in the following description are examples only, and the present invention is not limited to them, and can be implemented with appropriate modifications without changing the essence of the invention.

[0031] [In-mold molded product (3)] Figure 1 is a schematic cross-sectional view illustrating an example of an in-mold molded product according to this embodiment. As shown in Figure 1, the in-mold molded product 3 of this embodiment has a base sheet layer 1A (transparent base sheet layer (1A)) and an injection-molded resin layer 2 that is in contact with and integrated with the base sheet layer 1A.

[0032] In this embodiment, as a preferred example of the in-mold molded product 3 of this embodiment, the case in which the injection-molded resin layer 2 is in contact with and integrated with the base sheet layer 1A will be described. However, the injection-molded resin layer 2 only needs to be integrated with the base sheet layer 1A and does not need to be in contact with the base sheet layer 1A. Specifically, for example, a primer layer or the like may be formed between the injection-molded resin layer 2 and the base sheet layer 1A.

[0033] In this embodiment, as a preferred example of the in-mold molded product 3 of this embodiment, we will describe the case where the in-mold molded product 3 is an automobile bumper. The in-mold molded product 3 of this embodiment is manufactured using recycled plastic obtained by recycling a used bumper that was attached to a scrapped or repaired vehicle. Therefore, the in-mold molded product 3 of this embodiment is obtained through horizontal material recycling, which involves manufacturing the same part using recycled material obtained by recycling a discarded part.

[0034] In this embodiment, it is preferable that, when observing a rectangular area of ​​10 mm in length and 10 mm in width on the surface of the base sheet layer 1A opposite to the injection-molded resin layer 2 using a microscope at 20x magnification, 40 to 80 coating fragments with a maximum length of 0.25 mm or less, 2 to 10 coating fragments with a maximum length between 0.25 mm and 0.5 mm, and 1 or more coating fragments with a maximum length greater than 0.5 mm can be confirmed. When observing the above-mentioned area of ​​the in-mold molded product 3 at the above-mentioned magnification, if 40 or more coating fragments with a maximum length of 0.25 mm or less, 2 or more coating fragments between 0.25 mm and 0.5 mm in length, and 1 or more coating fragments exceeding 0.5 mm in length are observed, the number of coating fragments visible from the surface of the base sheet layer 1A side of the in-mold molded product 3 is significantly large. As a result, a visually appealing stardust-like pattern consisting of coating fragments is likely to form on the surface of the base sheet layer 1A side.

[0035] Furthermore, by observing the above-mentioned area of ​​the in-mold molded product 3 at the above-mentioned magnification, it can be confirmed that there are 70 or fewer paint film fragments with a maximum length of 0.25 mm or less, and 10 or fewer paint film fragments with a length exceeding 25 mm but 0.5 mm or less. This makes it easily visible that the product is made from recycled plastic obtained by recycling a discarded bumper that was attached to a scrapped or repaired vehicle, and also results in a product with excellent design.

[0036] In the in-mold molded product 3 of this embodiment, the average thickness in the lamination direction of the base sheet layer 1A and the injection-molded resin layer 2 is preferably 1.8 mm to 3.4 mm, and more preferably 2.0 mm to 2.5 mm. If the above average thickness is 1.8 mm or more, the in-mold molded product 3 will have better mechanical strength. If the above average thickness is 3.4 mm or less, the in-mold molded product 3 can be made lighter, making it more preferable as an automobile bumper.

[0037] (Base sheet layer (1A)) The base sheet layer 1A includes a transparent biaxially oriented polyolefin sheet 1a with a thickness of 60 μm or more, and the biaxially oriented polyolefin sheet 1a may be laminated with another transparent resin sheet. Examples of other transparent resin sheets include polycarbonate resin sheets, polyester resin sheets, and acrylic resin sheets, but in the present invention, it is preferable that the base sheet layer 1A is composed of the biaxially oriented polyolefin sheet 1a alone. In the in-mold molded product 3 of this embodiment, since the biaxially oriented polyolefin sheet 1a is transparent, the star-like pattern consisting of coating fragments contained in the injection-molded resin layer 2 can be seen from the surface of the base sheet layer 1A through the base sheet layer 1A. Furthermore, in the in-mold molded product 3 of this embodiment, since the biaxially oriented polyolefin sheet 1a is made by biaxial stretching, it has a high degree of crystallinity. In addition, since the thickness of the base sheet layer 1A is 60 μm or more, the in-mold molded product 3 of this embodiment has excellent flexural modulus, rigidity and impact strength, and has good mechanical strength. For example, if the injection-molded resin layer 2 is made of recycled plastic 2a obtained by recycling a waste bumper, the in-mold molded product 3 of this embodiment will have the same flexural modulus and impact strength as a bumper made of the same type of virgin material as the recycled plastic 2a. Furthermore, since the thickness of the base sheet layer 1A is 60 μm or more, the in-mold molded product 3 can be manufactured by the in-mold molding method even if it is made of a biaxially oriented polyolefin sheet 1a.

[0038] The thickness of the base sheet layer 1A is more preferably 90 μm or more, and even more preferably 150 μm or more, in order to further increase the mechanical strength of the in-mold molded product 3. Furthermore, the upper limit of the thickness of the base sheet layer 1A is not particularly limited and can be, for example, 400 μm or less. The thickness of the base sheet layer 1A is preferably 350 μm or less, and more preferably 300 μm or less, as it makes it easier to ensure a sufficient proportion of recycled plastic in the in-mold molded product 3 and improves moldability when molding using the in-mold molding method.

[0039] The base sheet layer 1A preferably has a crystallinity of 70% or more, more preferably 75% or more, and even more preferably 80% or more, due to X-ray diffraction when irradiated with X-rays from the cut surface. When the crystallinity is 70% or more, the in-mold molded product 3 has even better rigidity and impact strength, and good mechanical strength.

[0040] [Measurement of crystallinity by X-ray diffraction] The degree of crystallinity obtained by X-ray diffraction when X-rays are irradiated from the cut surface of the base sheet layer 1A of the in-mold molded product 3 can be measured using a known method, for example, by the method shown below. In other words, the degree of crystallinity can be calculated from the ratio of the peak area of ​​the crystalline component to the total peak area obtained by X-ray diffraction (peak area of ​​the crystalline component + halo pattern area of ​​the amorphous component). For example, it can be measured according to the Hermans-Weiding method described in Weidinger A. Hermans PH., Macromol Chem Phys [1961:50;98-115].

[0041] The biaxially oriented polyolefin sheet 1a forming the base sheet layer 1A may consist of a single polyolefin layer or multiple polyolefin layers. Here, if the biaxially oriented polyolefin sheet 1a consists of a single polyolefin layer, it is preferable that it consists of the polyolefin layer (A) shown below. If it is a multiple polyolefin layer, it is preferable that other polyolefin layers are laminated on polyolefin layer (A). Among these, it is preferable that polyolefin layer (A) shown below is laminated with polyolefin layer (B) having a lower melting point than polyolefin layer (A).

[0042] <Polyolefin layer (A)> The polyolefin layer (A) preferably contains a polyolefin polymer whose molecular weight distribution (weight-average molecular weight (Mw) / number-average molecular weight (Mn)) is in the range of 6 to 20. When the molecular weight distribution of the polyolefin polymer is within the above range, the polyolefin layer (A) has a uniform film thickness and possesses both high rigidity and excellent stretchability. Therefore, an in-mold molded product 3 having a base sheet layer 1A and a biaxially oriented polyolefin sheet 1a having a polyolefin layer (A) has better moldability during molding and possesses excellent mechanical strength.

[0043] The polyolefin layer (A) is preferably one in which the amount of xylene-insoluble matter is in the range of more than 96.5% by mass and 99.5% by mass or less. The xylene-insoluble matter contained in the polyolefin layer (A) corresponds to crystalline isotactic components. In contrast, the xylene-soluble components contained in the polyolefin layer (A) correspond to non-crystalline atactic components. The xylene-soluble components have a lower molecular weight compared to the xylene-insoluble matter. If the amount of xylene-insoluble matter in the polyolefin layer (A) exceeds 96.5% by mass, the rigidity and heat resistance of the in-mold molded product 3 containing the biaxially oriented polyolefin sheet 1a having the polyolefin layer (A) will be even better.

[0044] The polyolefin layer (A) preferably has a tacticity (stereoregularity (mmmm)) of xylene-insoluble components of 97.5% to 99.5%. When the stereoregularity (mmmm) of the xylene-insoluble components of the polyolefin layer (A) is 97.5% or higher, the in-mold molded product 3 including the base sheet layer 1A will have excellent rigidity and heat resistance.

[0045] The polyolefin layer (A) is preferably a sheet made of a polyolefin polymer such as polyethylene (PE), high-density polyethylene (high-density PE), ethylene-vinyl acetate copolymer resin (EVA), or polypropylene (PP). Among these sheets made of polyolefin polymers, the polyolefin layer (A) is preferably a sheet made of any polyolefin polymer selected from polypropylene homopolymer, propylene-containing copolymer obtained by polymerizing monomer components containing propylene, or a mixture of propylene copolymer and propylene homopolymer, in order to obtain an in-mold molded product 3 with good mechanical strength.

[0046] The propylene-containing copolymer as a polyolefin polymer may be a random copolymer, a block copolymer, or an alternating copolymer, but a random copolymer is preferred because it can be easily and efficiently produced. Examples of propylene-containing copolymers include a monomer component comprising propylene and at least one olefin selected from α-olefins having 2 to 10 carbon atoms, which is not an α-olefin having 3 carbon atoms, and having structural units derived from the monomer component containing the olefin that is not an α-olefin having 3 carbon atoms in a proportion of 7% by mass or less.

[0047] Among the propylene-containing copolymers mentioned above, ethylene-propylene copolymers having structural units derived from monomer components consisting of propylene and ethylene at a concentration of 3% by mass or less are particularly preferred. This is because they allow for the formation of biaxially oriented polyolefin sheets 1a that possess excellent rigidity and toughness, as well as good stretchability. As a result, the in-mold molded product 3 containing the base sheet layer 1A has good moldability during molding and also possesses excellent mechanical strength.

[0048] It is more preferable that the ethylene-propylene copolymer has a proportion of ethylene-derived structures in the structural units derived from the monomer component of 0.1% by mass or more and less than 1% by mass. In ethylene propylene copolymers, the lower limit of the proportion of ethylene-derived structures in structural units derived from monomer components is preferably 0.1% by mass or more, in order to obtain a polyolefin layer (A) with good transparency.

[0049] In ethylene-propylene copolymers, if the proportion of structures derived from ethylene in the structural units derived from monomer components is less than 1% by mass, a biaxially oriented polyolefin sheet 1a with superior rigidity and toughness can be formed. Preferably, the proportion of structures derived from ethylene in the structural units derived from monomer components is less than 0.6% by mass, and particularly preferably less than 0.3% by mass.

[0050] The polyolefin layer (A) preferably contains a transparent nucleating agent so that a biaxially oriented polyolefin sheet 1a with good transparency can be formed. The transparent nucleating agent refines the crystalline components in the polyolefin polymer forming the polyolefin layer (A), thereby improving the transparency of the biaxially oriented polyolefin sheet 1a containing the polyolefin layer (A).

[0051] Known transparent nucleating agents can be used. Specifically, one or more transparent nucleating agents selected from nonitol-based nucleating agents, sorbitol-based nucleating agents, phosphate ester-based nucleating agents, triaminobenzene derivative nucleating agents, carboxylate metal salt nucleating agents, and xylitol-based nucleating agents can be used. An example of a nonitol-based nucleating agent is 1,2,3-trideoxy-4,6:5,7-bis-[(4-propylphenyl)methylene]-nonitol. An example of a sorbitol-based nucleating agent is 1,3:2,4-bis-o-(3,4-dimethylbenzylidene)-D-sorbitol. An example of a phosphate ester-based nucleating agent is a lithium salt-based nucleating agent of phosphate-2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate.

[0052] The content of the transparent nucleating agent in the polyolefin layer (A) is preferably greater than 0 parts by mass and less than or equal to 1.0 part by mass per 100 parts by weight of the polyolefin polymer forming the polyolefin layer (A). If the content of the transparent nucleating agent per 100 parts by weight of the polyolefin polymer is greater than 0 parts by mass, the transparency of the biaxially oriented polyolefin sheet 1a containing the polyolefin layer (A) becomes even better. Furthermore, if the content of the transparent nucleating agent per 100 parts by weight of the polyolefin polymer is 1.0 part by mass or less, a biaxially oriented polyolefin sheet 1a can be formed that has excellent toughness and rigidity, can be easily molded, and has a uniform thickness.

[0053] The content of the transparent crystal nucleating agent is preferably 0.01 to 0.5 parts by mass, preferably 0.01 to 0.18 parts by mass, and particularly preferably 0.05 to 0.15 parts by mass, per 100 parts by weight of the polyolefin polymer forming the polyolefin layer (A).

[0054] The polyolefin layer (A) may contain known additives as long as they do not impair the effects of the present invention. Examples of additives include antioxidants, neutralizing agents, chlorine absorbers, heat stabilizers, light stabilizers, ultraviolet absorbers, internal lubricants, external lubricants, antiblocking agents, antistatic agents, antifogging agents, flame retardants, dispersants, copper damage inhibitors, plasticizers, crosslinking agents, peroxides, oil spreaders, organic pigments, and inorganic pigments.

[0055] <Polyolefin layer (B)> The polyolefin layer (B) only needs to have a melting point lower than that of the polyolefin layer (A), but specifically, it is preferable that it be composed of a polyolefin polymer with a melting point of 110 to 158°C. The melting point of the polyolefin layer (B) is the melting point measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min from 30°C to 230°C.

[0056] If the melting point of the polyolefin layer (B) is 158°C or lower, the melting point of the polyolefin layer (B) will be significantly lower than that of the polyolefin layer (A) described above. Therefore, when the polyolefin layer (B) is molded in contact with the injection-molded resin layer (2), good adhesion to the injection-molded resin layer (2) is achieved. Furthermore, for example, when multiple sheets having a multilayer structure in which layers B, A, and B are laminated in that order are stacked, and these are laminated and then heated and pressed to form a multilayer polyolefin layer, good fusion properties to the polyolefin layer (A) are observed.

[0057] The polyolefin polymer forming the polyolefin layer (B) is preferably a polypropylene-based resin. Specifically, the polyolefin polymer is preferably formed from a propylene homopolymer (HOMO); a propylene random copolymer (RACO) containing at least one comonomer selected from α-olefins having 2 to 10 carbon atoms, which is not an α-olefin having 3 carbon atoms, in an amount of 5% by mass or less; or a resin composition containing HOMO or RACO.

[0058] When the polyolefin layer (B) is made of propylene random copolymer (RACO), if the comonomer content is excessively low, the fusion between the polyolefin layer (B) and the aforementioned polyolefin layer (A) may be insufficient. On the other hand, if the comonomer content is excessively high, the rigidity of the biaxially oriented polyolefin sheet 1a, which consists of a multilayer polyolefin layer containing polyolefin layer (A) and polyolefin layer (B), may be insufficient. From this viewpoint, when the polyolefin layer (B) is made of propylene random copolymer (RACO), the comonomer content is preferably more than 0% by mass and 4.5% by weight or less. The comonomer is preferably ethylene (an α-olefin with 2 carbon atoms).

[0059] The polyolefin layer (B) may contain a transparent crystal nucleating agent because it can form a biaxially oriented polyolefin sheet 1a with good transparency. Known transparent crystal nucleating agents can be used, and specifically, one or more of the above-mentioned transparent crystal nucleating agents that may be contained in the polyolefin layer (A) can be used. When the polyolefin layer (B) contains a transparent crystal nucleating agent, the content of the transparent crystal nucleating agent is preferably 1.00 part by mass or less, and more preferably 0.18 parts by mass or less, per 100 parts by weight of the polyolefin polymer forming the polyolefin layer (B).

[0060] If the biaxially oriented polyolefin sheet 1a consists of a multilayer polyolefin layer formed by laminating one or more of the above-described polyolefin layers (A) (hereinafter also referred to as "(A) layer") and one or more of the above-described polyolefin layers (B) (hereinafter also referred to as "(B) layer"), then it can be configured as a two-layer structure of (A) layer / (B) layer (ab type), a three-layer structure of (B) layer / (A) layer / (B) layer (bab type), etc., and can be appropriately selected according to the desired strength, etc.

[0061] When the in-mold molded product 3 of this embodiment is used as an automotive exterior component such as a car bumper, it is preferable to use a multilayer polyolefin sheet 1a in which layer (A) is located as the outermost layer, and to have layer (A) on the outer surface and layer (B) on the inner surface (the surface in contact with the injection-molded resin layer (2)) of the in-mold molded product 3, in order to have good surface hardness and good adhesion with the injection-molded resin layer (2).

[0062] In this embodiment, if the biaxially oriented polyolefin sheet 1a consists of a multilayer polyolefin layer comprising one or more polyolefin layers (A) and one or more polyolefin layers (B), it is preferable that the thickness of the polyolefin layer (A) is 60 μm or more.

[0063] Furthermore, in a multilayer polyolefin layer in which one or more polyolefin layers (A) and one or more polyolefin layers (B) are laminated, it is preferable that the ratio of the thickness of layer (A) to the thickness of layer (B) is higher. This is because it results in a biaxially oriented polyolefin sheet 1a with excellent toughness and mechanical strength, and an in-mold molded product 3 with excellent properties. Specifically, when the biaxially oriented polyolefin sheet 1a has a two-layer structure of layer (A) / layer (B), it is preferable that the thickness of layer (A) / layer (B) is 98~80 / 2~20, and in particular, that the thickness of layer (A) / layer (B) is 98~90 / 2~10, as this results in superior strength for the in-mold molded product 3. When the biaxially oriented polyolefin sheet 1a has a three-layer structure (bab type) of (B) layer / (A) layer / (B) layer, it is preferable that the thickness of the (B) layer / thickness of the (A) layer / thickness of the (B) layer is 2~15 / 96~70 / 2~15.

[0064] (Method for manufacturing a biaxially oriented polyolefin sheet (1a)) The biaxially oriented polyolefin sheet 1a can be manufactured, for example, by the method shown below. First, an unstretched sheet that will become a biaxially oriented polyolefin sheet 1a is formed by a known method.

[0065] When producing a biaxially oriented polyolefin sheet 1a consisting of a single polyolefin layer (A), for example, an extruder is used to extrude a polyolefin composition (a) that will become the polyolefin layer (A), and it is formed into a sheet by a known method to form an unstretched sheet.

[0066] Furthermore, when manufacturing a biaxially oriented polyolefin sheet 1a consisting of a multilayer polyolefin layer in which one or more polyolefin layers (A) and one or more polyolefin layers (B) are laminated, a polyolefin composition (a) that will become polyolefin layer (A) and a polyolefin composition (b) that will become polyolefin layer (B) are prepared. Then, the polyolefin composition (a) and polyolefin composition (b) are co-extruded from an extruder into a multilayer T-die and formed into a sheet using a known method, etc., to form an unstretched sheet. Known methods such as the feed block method and the multi-manifold method can be used as co-extrusion methods.

[0067] (Polyolefin composition (a)) The polyolefin composition (a) that forms the polyolefin layer (A) of the biaxially oriented polyolefin sheet 1a comprises a polyolefin polymer corresponding to the polyolefin polymer contained in the polyolefin layer (A), a transparent crystal nucleating agent, and other additives as needed.

[0068] The polyolefin composition (a) has a melt flow rate (MFR) of 1 g / 10 min to 15 g / 10 min, preferably 2 g / 10 min to 6 g / 10 min, under conditions of applying a load of 2.16 kgf at a temperature of 230 °C.

[0069] The polyolefin composition (a) preferably has a crystallization rate parameter (t1 / 2) greater than 1 second, and more preferably 2 seconds or more. The crystallization rate parameter (t1 / 2) of the polyolefin composition (a) increases as the crystallization rate of the polyolefin composition (a) decreases. The crystallization rate of the polyolefin composition (a) tends to decrease as the content of the transparent nucleating agent contained in the polyolefin composition (a) decreases. When the crystallization rate parameter (t1 / 2) of the polyolefin composition (a) exceeds 1 second, it becomes easier to obtain a polyolefin layer (A) of uniform thickness. The upper limit of the crystallization rate parameter (t1 / 2) of the polyolefin composition (a) is not particularly limited, but it is preferably 5 seconds or less.

[0070] (Polyolefin composition (b)) The polyolefin composition (b) that forms the polyolefin layer (B) of the biaxially oriented polyolefin sheet 1a comprises a polyolefin polymer corresponding to the polyolefin polymer contained in the polyolefin layer (B), a transparent crystal nucleating agent as needed, and an additive that is not a transparent crystal nucleating agent as needed.

[0071] The polyolefin composition (b) preferably has a melt flow rate (MFR) of 1 g / 10 min to 15 g / 10 min, more preferably 2 g / 10 min to 10 g / 10 min, and even more preferably 3 g / 10 min to 8 g / 10 min, under conditions of a load of 2.16 kgf at a temperature of 230 °C.

[0072] In this embodiment, as a method for forming a polyolefin composition (polyolefin composition (a) and polyolefin composition (b), or polyolefin composition (a) only) into a sheet to become a biaxially oriented polyolefin sheet 1a, an example can be used to extrude the polyolefin composition using a known extruder and draw it into a sheet using a cast roll. The thickness of the unstretched sheet can be, for example, in the range of 0.5 mm to 5 mm.

[0073] Next, the unstretched sheet produced by the above method is biaxially stretched. In this embodiment, the degree of crystallinity of the biaxially oriented polyolefin sheet (1a) obtained by biaxially oriented an unstretched sheet obtained by forming a polyolefin composition into a sheet is adjusted by adjusting the stretching conditions, so that the degree of crystallinity obtained by X-ray diffraction when X-rays are irradiated from the cut surface of the biaxially oriented polyolefin sheet (1a) is appropriate.

[0074] In this embodiment, when biaxially stretching an unstretched sheet obtained by forming a polyolefin composition into a sheet, the stretching ratio in the TD direction can be, for example, 3 to 10 times, preferably 3.5 to 8 times, and more preferably 4 to 7 times. Also, when biaxially stretching the unstretched sheet, the stretching ratio in the MD direction can be, for example, 3 to 6 times, preferably 3.5 to 8 times, and more preferably 4 to 7 times. By setting the stretching ratio in the TD direction to 3 to 10 times and the stretching ratio in the MD direction to 3 to 6 times during biaxial stretching, a biaxially oriented polyolefin sheet 1a with better mechanical strength is obtained.

[0075] When biaxially stretching an unstretched sheet, it is preferable that the stretching ratios in the TD direction and the MD direction are the same. This is because biaxial stretching of the unstretched sheet results in a biaxially oriented polyolefin sheet 1a with low anisotropy in orientation, and the in-mold molded product 3 including the base sheet layer 1A has less distortion and good shape stability.

[0076] Furthermore, as a method for biaxially stretching an unstretched sheet obtained by forming a polyolefin composition into a sheet, sequential biaxial stretching or simultaneous biaxial stretching can be used, and simultaneous biaxial stretching is preferred. The reason for this is that the TD direction and MD direction can be stretched simultaneously at an equivalent ratio, resulting in a biaxially oriented polyolefin sheet 1a with very little anisotropy in orientation due to biaxial stretching of the unstretched sheet. As a result, the moldability is good when forming an in-mold molded product 3 including the base sheet layer 1A. Furthermore, when using the simultaneous biaxial stretching method, it is easier to obtain an in-mold molded product 3 with superior physical strength and shape stability compared to when using the sequential biaxial stretching method. In addition, when using the simultaneous biaxial stretching method, scratches associated with stretching are less likely to occur on the surface of the biaxially oriented polyolefin sheet 1a compared to when using the sequential biaxial stretching method, which is preferable. Furthermore, when using the simultaneous biaxial stretching method, the sheet stretched in the first stretching direction is not cooled before being stretched in the second stretching direction, as is the case when using the sequential biaxial stretching method, and therefore, adverse effects due to crystallization caused by cooling are avoided, which is preferable.

[0077] (Injection molded resin layer (2)) The injection-molded resin layer 2 is manufactured using recycled plastic 2a obtained by recycling a scrapped or repaired bumper, and consists of a resin material which is recycled plastic 2a containing paint fragments derived from the surface coating of the scrapped plastic. The recycled plastic 2a obtained by recycling a scrapped bumper contains a moderate amount of paint fragments derived from the surface coating. Therefore, it is preferable that an in-mold molded product 3 with good design is easily obtained. Recycled plastic 2a, which is made by recycling waste bumpers, can be manufactured using a known method of crushing and melting waste bumpers.

[0078] In this embodiment, recycled plastic 2a is used as the resin material forming the injection-molded resin layer 2. That is, the recycled plastic 2a content in the resin material is 100% by mass. It is preferable that the resin material forming the injection-molded resin layer 2 in this embodiment consists solely of recycled plastic 2a. This is because it increases the content of coating fragments derived from the surface coating, making it easier to obtain an in-mold molded product 3 with good design, and also increases the recycling rate.

[0079] The resin material forming the injection-molded resin layer 2 in this embodiment may, if necessary, contain a resin material other than recycled plastic 2a along with recycled plastic 2a. The content of the resin material other than recycled plastic 2a can be, for example, 70% by mass or less, and preferably 35% by mass or less. When the content of the resin material other than recycled plastic 2a is 70% by mass or less, the content of coating fragments derived from the surface coating becomes sufficiently large, making it easier to obtain an in-mold molded product 3 with good design and ensuring a high recycling rate.

[0080] As a resin material other than recycled plastic 2a, for example, a virgin material of the same type as recycled plastic 2a can be used. By using a virgin material of the same type as recycled plastic 2a as a resin material, the mechanical strength of the in-mold molded product 3 can be further improved. For recycled plastic 2a and virgin material to be of the same type means that the structure derived from the most abundant monomer component among the structural units of the polyolefin polymer that forms them is the same in recycled plastic 2a and virgin material.

[0081] Polyolefin polymers are generally used as materials for plastic vehicle bumpers, and in particular, polypropylene homopolymers and propylene-containing copolymers obtained by polymerizing monomer components containing propylene are widely used. Therefore, if recycled plastic 2a is recycled plastic obtained by recycling a waste bumper, it is preferable to use polypropylene homopolymer and / or propylene-containing copolymer as the resin material other than recycled plastic 2a.

[0082] The injection-molded resin layer 2 is formed by an in-mold molding method and is integrated with the base sheet layer 1A in contact with it, as shown in Figure 1. The injection-molded resin layer 2 is sufficiently thin, and is positioned in contact with the base sheet layer 1A in the thickness direction. This ensures that the flow direction (MD direction) of the resin material during molding is aligned with the sheet surface of the base sheet layer 1A. As a result, the coating fragments contained in the injection-molded resin layer 2 are oriented such that the area visible from the surface of the base sheet layer 1A is greater than the area of ​​the coating fragments appearing in the cross-sectional direction of the base sheet layer 1A. Consequently, the in-mold molded product 3 of this embodiment has excellent aesthetic appeal.

[0083] [Manufacturing method for in-mold molded product (3)] Next, the method for manufacturing the in-mold molded article 3 of the present invention will be explained with an example. Figures 2 and 3 are schematic process diagrams illustrating the manufacturing method of the in-mold molded product 3 shown in Figure 1. To manufacture the in-mold molded product 3 shown in Figure 1, first, a transparent biaxially oriented polyolefin sheet 1a with a thickness of 60 μm or more is prepared.

[0084] Next, the biaxially oriented polyolefin sheet 1a is shaped to conform to the shape inside the cavity 44 by known methods such as vacuum forming, vacuum pressure forming, or press forming. The biaxially oriented polyolefin sheet 1a used in this embodiment has a thickness of 60 μm or more. Therefore, the biaxially oriented polyolefin sheet 1a can be shaped by known methods. By shaping the biaxially oriented polyolefin sheet 1a to conform to the shape inside the cavity 44 and then placing it inside the cavity 44 of the mold 4, the biaxially oriented polyolefin sheet 1a can be accurately placed in a predetermined position inside the cavity 44.

[0085] Furthermore, a mold 4 is prepared for the manufacture of the in-mold molded product 3. As the mold 4, for example, as shown in Figure 2, a first mold 41 can be used, which has a second mold 42 positioned opposite the first mold 41 to form a cavity, and an injection port 43 that penetrates the second mold 42. The cavity of the mold 4 shown in Figure 2 (see reference numeral 44 in Figure 3) has a shape that corresponds to the outer shape of the in-mold molded product 3.

[0086] As shown in Figure 2, the injection port 43 of the mold 4 is located near the vertical end of Figure 2, approximately at the center of the depth direction in a plan view, and is positioned so as not to overlap with the position where the biaxially oriented polyolefin sheet 1a is installed when viewed from the thickness direction of the automobile bumper. As a result, no marks originating from the injection port 43 of the mold 4 are formed on the molded in-mold product 3, and the resin material injected from the injection port 43 flows more easily along the sheet surface of the biaxially oriented polyolefin sheet 1a.

[0087] Next, the biaxially oriented polyolefin sheet 1a is placed in the cavity 44 of the mold 4 (sheet placement step). Specifically, the biaxially oriented polyolefin sheet 1a, which is shaped to conform to the shape inside the cavity 44, is placed on the cavity 44 side surface of the first mold 41, which is positioned opposite the second mold 42, where the injection port 43 of the mold 4 is provided. If the biaxially oriented polyolefin sheet 1a consists of a multilayer polyolefin layer in which one or more polyolefin layers (A) and one or more polyolefin layers (B) are laminated, with layer (A) being the outermost layer, it is preferable to place the biaxially oriented polyolefin sheet 1a so that the polyolefin layer (A) is in contact with the mold.

[0088] Then, as shown in Figure 3, the first mold 41 and the second mold 42 of the mold 4 are placed opposite each other to form a cavity 44. Subsequently, as shown in Figure 3, a resin material containing recycled plastic 2a, which includes coating fragments derived from the surface coating of waste plastic, is injected from the injection port 43 of the mold 4 into the cavity 44 and molded (molding process).

[0089] In this embodiment, during the molding process, the resin material is injected into the cavity 44 so as to flow in a direction along the sheet surface of the biaxially oriented polyolefin sheet 1a. Specifically, as shown in Figure 2, the resin material injected into the cavity 44 from the injection port 43 of the mold 4 flows toward the first mold 41 and abuts against the biaxially oriented polyolefin sheet 1a installed on the cavity 44 side of the first mold 41. Then, it flows through the gap between the first mold 41 and the second mold 42 toward the end opposite to the side where the injection port 43 is located in the longitudinal direction (up and down direction in Figure 3) of the automobile bumper, along the direction along the sheet surface of the biaxially oriented polyolefin sheet 1a.

[0090] When the resin material is injected into the cavity 44 from the injection port 43 of the mold 4, the temperature of the resin material is preferably in the range of 180°C to 280°C when recycled plastic 2a obtained by recycling a used bumper that was attached to a scrapped or repaired vehicle is used as the resin material. When the temperature of the resin material is 180°C or higher, the fluidity of the resin material is good, and excellent moldability can be obtained. The temperature of the resin material when injecting is preferably 200°C to 280°C, as this results in better adhesion, and is particularly preferably 220°C to 280°C.

[0091] After injecting the resin material into the cavity 44, it is cooled using a known method. This hardens the resin material to form an injection-molded resin layer 2, and integrates the injection-molded resin layer 2 with the base sheet layer 1A to form an in-mold molded product 3. Subsequently, the in-mold molded product 3 is removed from the mold 4. By performing the above steps, the in-mold molded product 3 shown in Figure 1 is obtained.

[0092] [Other examples] The embodiments of the present invention have been described above, but these embodiments are provided to facilitate understanding of the present invention and do not limit it. The present invention can be modified and improved without departing from its spirit and claims, and of course, equivalents thereof are included in the present invention.

[0093] In the embodiments described above, an automobile bumper was used as a preferred example of the in-mold molded article 3 and its manufacturing method. However, the applications of the in-mold molded article and its manufacturing method of the present invention are not limited to automobile bumpers.

[0094] The in-mold molded product of the present invention may be, for example, an automotive exterior component such as a front pillar (A-pillar), center pillar (B-pillar), rear pillar (C-pillar), front door panel, rear door panel, back door panel, roof material, hood, fender, etc.; an automotive interior component such as a dashboard, center cluster, door trim, etc.; a home appliance casing such as a refrigerator casing, a freezer casing, etc.; an electronic device casing such as a smartphone casing, a PC casing, etc.; a solar cell back sheet, etc.

[0095] Furthermore, in the embodiments described above, the recycled plastic 2a used when manufacturing the in-mold molded product 3 was described as including recycled plastic obtained by recycling a scrapped bumper that was attached to a scrapped or repaired vehicle. However, the recycled plastic 2a is not limited to recycled plastic obtained by recycling a scrapped bumper, and may include paint fragments derived from the surface coating of the scrapped plastic. The recycled plastic used in manufacturing the in-mold molded articles of the present invention may, for example, be recycled plastic obtained by recycling products that have been used in the above-described applications and then discarded.

[0096] Furthermore, the in-mold molded article of the present invention may have a base sheet layer 1A and an injection-molded resin layer 2 that is in contact with and integrated with the base sheet layer 1A. For example, a hard coat layer may be provided on the side of the base sheet layer 1A opposite to the injection-molded resin layer 2. By providing a hard coat layer, an in-mold molded article with good scratch resistance can be obtained. The hard coat layer may contain additives such as known weather-resistant agents and flame retardants. This allows for the imparting of various functions to in-mold molded products. [Examples]

[0097] [Example 1] (Method for manufacturing a biaxially oriented polyolefin sheet (1a)) A biaxially oriented polyolefin sheet 1a was produced using the method described below, which consisted of a multilayer polyolefin structure in which one polyolefin layer (A) and one polyolefin layer (B) were laminated together. First, a polyolefin composition (a) which will form the polyolefin layer (A) and a polyolefin composition (b) which will form the polyolefin layer (B) were prepared as shown below.

[0098] The polyolefin composition (a) used in Example 1 contains an ethylene propylene copolymer (melting point: 165°C) as the polyolefin polymer, in which the proportion of structures derived from ethylene in the structural units derived from the monomer component is 0.2% by mass. The molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the ethylene propylene copolymer is 9. The polyolefin composition (a) has a xylene-insoluble content of 98.2% by mass, and the stereoregularity (mmmm) of the xylene-insoluble content is 98.3%. Furthermore, the polyolefin composition (a) contains a transparent crystal nucleating agent at a ratio of 0.05% by mass per 100 parts by weight of the ethylene propylene copolymer, and the crystallization rate parameter (t1 / 2) is 2.3 seconds. The melt flow rate (MFR) of the polyolefin composition (a) is 5 g / min under conditions of applying a load of 2.16 kgf at a temperature of 230°C.

[0099] The polyolefin composition (b) used in Example 1 contains an ethylene-propylene random copolymer (melting point 150°C). The polyolefin composition (b) has a melt flow rate (MFR) of 6 g / min at a temperature of 230°C with a load of 2.16 kgf applied.

[0100] The polyolefin composition (a) and polyolefin composition (b) described above were melt-kneaded in an extruder, co-extruded from the extruder into a multilayer T-die with a lip opening width of 3 mm, and formed into a sheet by drawing it out with a cast roll to obtain an unstretched sheet in which one polyolefin layer (A) and one polyolefin layer (B) were laminated.

[0101] Subsequently, the obtained unstretched sheet was biaxially stretched using a simultaneous biaxial stretching method, with stretch ratios of 5x in the MD direction and 5x in the TD direction, while adjusting the temperature as appropriate within the temperature range of 140°C to 180°C to reduce the stretch ratio by 29% from the maximum stretch ratio. This resulted in a biaxially oriented polyolefin sheet (1a) of Example 1, in which the ratio of the thickness of the polyolefin layer (A) to the polyolefin layer (B) (thickness of layer (A) / thickness of layer (B)) was 95 / 5 and the total thickness was 0.2 mm.

[0102] [Example 2] Except for making the thickness of the biaxially oriented polyolefin sheet (1a) 0.3 mm, a biaxially oriented polyolefin sheet (1a) of Example 2 with a thickness of 0.3 mm was obtained in the same manner as in Example 1.

[0103] [Measurement of crystallinity of biaxially oriented polyolefin sheet (1a)] The biaxially oriented polyolefin sheets (1a) of Example 1 and Example 2 were each cut in the TD direction to obtain measurement samples. The obtained measurement samples were placed in an X-ray diffraction apparatus so that X-rays struck the cut surface, and the degree of crystallinity by X-ray diffraction when X-rays were irradiated from the cut surface was measured according to the Hermans-Weidinger method. As a result, the degree of crystallinity determined by X-ray diffraction when X-rays were irradiated from the cross-section of the biaxially oriented polyolefin sheet (1a) was 85% for Example 1 and 85% for Example 2.

[0104] [Example 3] (Method for manufacturing in-mold molded product (3)) A mold was prepared comprising a first mold, a second mold positioned opposite the first mold to form a roughly square cavity in plan view, and a joint between the first and second molds, with an injection port located approximately in the center of one side of the roughly square cavity in plan view. The inside of the mold cavity has a roughly square shape with dimensions of 350 mm in length and 350 mm in width in plan view. The thickness inside the cavity can be 2 mm or 3 mm.

[0105] In a mold cavity that is approximately square in plan view, the direction approximately perpendicular to the side where the injection port is located is the flow direction of the resin material during molding (MD direction), and the direction in which the side where the injection port is located extends is the TD direction, which is perpendicular to the MD direction. Next, the biaxially oriented polyolefin sheet 1a of Example 1 was shaped to conform to the shape of the cavity in the mold by vacuum forming. At this time, the polyolefin layer (A) side of the biaxially oriented polyolefin sheet 1a was shaped to be convex.

[0106] Subsequently, the biaxially oriented polyolefin sheet (1a) of Example 1, which was shaped to conform to the shape inside the cavity, was placed on the cavity-side surface of the first mold so that the polyolefin layer (A) side of the biaxially oriented polyolefin sheet 1a was in contact with the mold. Then, the first and second molds were placed facing each other to form a cavity that was roughly square in plan view.

[0107] Subsequently, a resin material containing recycled plastic (2a) was injected into the cavity from the mold's injection port and molded. The temperature of the resin material when injected into the cavity from the mold's injection port was 230°C. Furthermore, as recycled plastic (2a), recycled plastic was used obtained by recycling waste bumpers made of propylene-containing copolymer that had been attached to scrapped or repaired vehicles.

[0108] In Example 3, the resin material injected into the cavity from the mold's injection port flows along the sheet surface of the biaxially oriented polyolefin sheet (1a) through the gap between the first and second molds, towards the side opposite the side where the injection port is located in the cavity, which is approximately square in plan view.

[0109] After injecting the resin material into the cavity, it was cooled. This cured the resin material to form an injection-molded resin layer (2), and integrated the injection-molded resin layer (2) with the base sheet layer (1A) to form an in-mold molded product (3). Subsequently, the in-mold molded product (3) was removed from the mold, and an in-mold molded product (3) of Example 3 with dimensions of 350 mm in length, 350 mm in width, and 2 mm in thickness was obtained.

[0110] [Example 4] An in-mold molded product (3) of Example 4, measuring 350 mm in length, 350 mm in width, and 2 mm in thickness, was obtained in the same manner as in Example 3, except that a biaxially oriented polyolefin sheet (1a) of Example 2 with a thickness of 0.3 mm was used instead of the biaxially oriented polyolefin sheet (1a) of Example 1.

[0111] [Example 5] Except for increasing the amount of resin material containing recycled plastic (2a) injected and setting the thickness to 3 mm, an in-mold molded product (3) of Example 5 with dimensions of 350 mm in length, 350 mm in width, and 3 mm in thickness was obtained in the same manner as in Example 3.

[0112] [Example 6] Except for increasing the amount of resin material containing recycled plastic (2a) injected and setting the thickness to 3 mm, an in-mold molded product (3) of Example 6, measuring 350 mm in length, 350 mm in width, and 3 mm in thickness, was obtained in the same manner as in Example 4.

[0113] [Comparative Example 1] A molded product of Comparative Example 1, measuring 350 mm in length, 350 mm in width, and 2 mm in thickness, was obtained in the same manner as in Example 3, except that a cavity was formed without installing a biaxially oriented polyolefin sheet (1a), and a resin material consisting of polypropylene, talc filler, etc., was injected into the cavity from the injection port of the mold instead of recycled plastic (2a).

[0114] [Comparative Example 2] A molded product of Comparative Example 1, measuring 350 mm in length, 350 mm in width, and 2 mm in thickness, was obtained in the same manner as in Example 3, except that a cavity was formed without installing a biaxially oriented polyolefin sheet (1a), and a resin material containing recycled plastic (2a) was injected into the cavity from the injection port of the mold.

[0115] [Comparative Example 3] Except for increasing the amount of resin material injected and setting the thickness to 3 mm, the same procedure as in Comparative Example 1 was used to obtain a molded product of Comparative Example 1 with dimensions of 350 mm in length, 350 mm in width, and 3 mm in thickness.

[0116] [Comparative Example 4] Except for increasing the amount of resin material containing recycled plastic (2a) injected and setting the thickness to 3 mm, a molded product of Comparative Example 2 with dimensions of 350 mm in length, 350 mm in width, and 3 mm in thickness was obtained in the same manner as Comparative Example 2.

[0117] [Measurement of the degree of crystallinity of biaxially oriented polyolefin sheet (1a) contained in molded products] The molded products of Examples 3-6 and Comparative Examples 1-4 were each cut near the center to obtain measurement samples. The obtained measurement samples were placed in an X-ray diffraction apparatus so that X-rays struck the biaxially oriented polyolefin sheet (1a) exposed on the cut surface, and the degree of crystallinity by X-ray diffraction when X-rays were irradiated from the cut surface was measured according to the Hermans-Weidinger method. The results are shown in Table 1.

[0118] [Table 1]

[0119] Furthermore, the flexural modulus in the MD direction, impact bank cher energy (23°C) (-30°C), and flexural modulus in the TD direction were measured for the molded products of Examples 3-6 and Comparative Examples 1-4 using the method described below. The results are shown in Table 1. Also, the bending test force in the MD direction and the bending test force in the TD direction for the molded products of Examples 3-6 and Comparative Examples 1-4 are shown in Table 1.

[0120] [Flexural modulus (MD direction) (TD direction)] In accordance with JIS K7171, the tensile test modulus in the MD and TD directions was measured under the following conditions. • Equipment used: AUTOGRAPH AG-X plus (manufactured by Shimadzu Corporation) • Test specimen: A rectangular test specimen measuring 25 mm in length and 150 mm in width. • Support distance: 16 times the thickness of the test specimen • Test speed: 1 mm / min • Stroke: 1mm • Method for calculating elastic modulus: Inclination of two points at strokes of 0.05 mm and 0.25 mm. • Plot sampling start point: 3N

[0121] [Surface impact strength (23℃) (-30℃)] The test was conducted in accordance with JIS K7211-2, under the following conditions: striker diameter: 20 mm, receiving diameter: 40 mm, and test speed: 4.4 m / sec. The test specimen was set up at a temperature of 23°C or -30°C, and the test was performed after the specimen had stabilized in temperature. The impact puncture energy (unit: J (joules)) was calculated by analyzing the range of half the point of maximum impact force application.

[0122] As shown in Table 1, in the molded articles of Examples 3 to 6, it was confirmed that, if the thickness of the molded articles was the same, equivalent or better flexural modulus and impact puncture energy could be obtained compared to the molded articles of Comparative Examples 1 and 3, which did not use biaxially oriented polyolefin sheets (1a) and used resin materials consisting of virgin polypropylene, talc filler, etc. Furthermore, as shown in Table 1, it was confirmed that the molded articles of Examples 3 to 6 obtained superior flexural modulus and impact puncture energy compared to the molded articles of Comparative Examples 2 and 4, which did not use biaxially oriented polyolefin sheets (1a) but used recycled plastic (2a).

[0123] As shown in Table 1, it was confirmed that the molded articles of Example 4 and Example 6 obtained superior flexural modulus and impact puncture energy compared to the molded articles of Example 3 and Example 5, which had different thicknesses of biaxially oriented polyolefin sheet (1a). Furthermore, it was confirmed that the molded products of Examples 5 and 6 exhibited superior flexural modulus and impact puncture energy compared to the molded products of Examples 3 and 4, which had different thicknesses.

[0124] Furthermore, the surface of the base sheet layer (1A) side of the molded product in Example 3 and the surface of one side of the molded product in Comparative Example 2 were subjected to surface roughness measurement, visual observation, microscope observation, and cross-sectional observation using the methods described below.

[0125] [Surface roughness measurement] Two rectangular measurement samples, each measuring 10 mm in length and 10 mm in width, were cut from the molded product of Example 3 and the molded product of Comparative Example 2. For each measurement sample, the surface roughness was measured using a VK-X250 (manufactured by Keyence Corporation) in accordance with JIS B 0601-2001. Specifically, the measurement was performed in the range from the center of each measurement sample to a position moved 288 μm in the TD direction from the measurement start point. The obtained measurement results were then analyzed using cutoff values ​​of λs = 2.5 μm and λc = 0.8 mm to remove noise and waviness, and the surface roughness (Ra) was calculated. Subsequently, the average value of the surface roughness (Ra) of the two measurement samples was calculated.

[0126] As a result, the surface roughness Ra of the molded product in Example 3 was 0.09 μm, and the surface roughness Ra of the molded product in Comparative Example 2 was 0.18 μm. This confirmed that the molded product of Example 3 had fewer irregularities compared to the molded product of Comparative Example 2, which used recycled plastic (2a) instead of biaxially oriented polyolefin sheet (1a).

[0127] [External observation] The results of the external appearance photographs are shown in Figures 4 and 5. Figure 4 is a photograph of the surface of the molded product of Example 3, specifically the side with the base sheet layer (1A). Figure 5 is a photograph of one side of the molded product of Comparative Example 2. As shown in Figures 4 and 5, the surface of the molded product in Example 3 on the substrate sheet layer (1A) side showed significantly more noticeable coating fragments compared to the surface of one side of the molded product in Comparative Example 2.

[0128] [Microscope observation] Figure 12 shows the observation positions using a microscope on the molded products of Example 3 and Comparative Example 2. Using a microscope (product name: VHX-X1, manufactured by Keyence Corporation), the surface of the base sheet layer (1A) side of the molded product of Example 3 and the surface of one side of the molded product of Comparative Example 2 were observed at a magnification of 20x at two locations in the center of the extending direction of the side where the injection port is provided (hereinafter referred to as "center 1" and "center 2"; see Figure 12), and one location each near two opposing sides perpendicular to the side where the injection port is provided (hereinafter referred to as "side 1" and "side 2"; see Figure 12). Images were then obtained for the molded product of Example 3 and the molded product of Comparative Example 2 within rectangular areas of 10 mm vertically and 10 mm horizontally in center 1, center 2, side 1, and side 2, respectively.

[0129] The obtained images of central section 1, central section 2, side section 1, and side section 2 were analyzed using image analysis software (product name: PopImaging, manufactured by Digital Being Kids Co., Ltd.) to measure the number of paint film fragments and the maximum length of each fragment. The number of confirmed paint film fragments was then tallied for each fragment whose maximum length fell within the following ranges: over 0.00 mm to 0.25 mm, over 0.25 mm to 0.50 mm, over 0.50 mm to 0.75 mm, and over 0.75 mm to 1.00 mm. The results are shown in Figures 6 to 9.

[0130] Figure 6 shows the results of microscopic observation of the central portion 1 in the molded products of Example 3 and Comparative Example 2. Figure 7 shows the results of microscopic observation of the central portion 2 in the molded products of Example 3 and Comparative Example 2. Figure 8 shows the results of microscopic observation of side portion 1 in the molded products of Example 3 and Comparative Example 2. Figure 9 shows the results of microscopic observation of side portion 2 in the molded products of Example 3 and Comparative Example 2. In Figures 6 to 9, (a) is an image of the molded products of Example 3 and Comparative Example 2 observed with a microscope at 20x magnification. (b) is an image of the image of (a) of Example 3 and Comparative Example 2 analyzed using image analysis software. (c) is a graph showing the relationship between the number of coating fragments and the maximum length of the coating fragments in the molded products of Example 3 and Comparative Example 2.

[0131] As shown in Figures 6 to 9, in all of the central section 1, central section 2, side section 1, and side section 2, the surface on the substrate sheet layer (1A) side of the molded product of Example 3 had a larger number of coating fragments and a longer maximum length for each visible coating fragment compared to the surface on one side of the molded product of Comparative Example 2. Furthermore, as shown in Figures 6 to 9, no significant differences were observed in the molded products of Example 3 and Comparative Example 2 depending on the observation position.

[0132] [Cross-sectional observation] On the surface of the molded product of Example 3 on the substrate sheet layer (1A) side, and on one side of the molded product of Comparative Example 2, the largest visible coating fragment was selected. Next, the molded product of Example 3 and the molded product of Comparative Example 2 were cut so that the central part of the selected large-area coating fragment was cut. The cross-sections of each cut molded product were then observed using a scanning electron microscope (SEM): (product name: JSM-IT700HR, manufactured by JEOL Ltd.). The results are shown in Figures 10 and 11.

[0133] Figure 10(a) is an SEM image of a cross-section of the molded product of Example 3. Figure 10(b) is a photograph of a large coating film fragment visible on the surface of the molded product of Example 3. The arrow pointing from bottom to top in Figure 10(b) indicates the MD direction. Figure 11(a) is an SEM image of a cross-section of Comparative Example 2. Figure 11(b) is a photograph of a large coating film fragment visible on the surface of the molded product of Comparative Example 2. The arrow pointing from bottom to top in Figure 11(b) indicates the MD direction.

[0134] As shown in Figures 10(a) and 11(a), in the molded product of Example 3, compared to the molded product of Comparative Example 2, the orientation of the coating fragments tends to be aligned such that the area of ​​coating fragments visible from the surface on the base sheet layer (1A) side is larger than the area of ​​coating fragments appearing in the cross-sectional direction of the base sheet layer (1A). More specifically, the recycled plastic in the molded products of Example 3 and Comparative Example 2 contains many coating fragments with shapes such as rods and columns. However, in the molded product of Example 3, compared to the molded product of Comparative Example 2, the coating fragments tend to be arranged with their length aligned along the surface of the molded product. [Explanation of Symbols]

[0135] 1A...Base sheet layer (transparent base sheet layer), 1a...Biaxially oriented polyolefin sheet, 2...Injection molded resin layer, 2a...Recycled plastic, 3...In-mold molded product, 4...Mold, 41...First mold, 42...Second mold, 43...Injection port, 44...Cavity.

Claims

1. A transparent substrate sheet layer (1A) containing a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more, An in-mold molded product comprising an injection-molded resin layer (2) made of a resin material that is integrated with the transparent substrate sheet layer (1A) and contains recycled plastic (2a) including coating fragments derived from the surface coating of waste plastic.

2. The in-mold molded article according to claim 1, wherein the transparent substrate sheet layer (1A) has a crystallinity of 70% or more due to X-ray diffraction when irradiated with X-rays from the cut surface.

3. The in-mold molded product according to claim 1, wherein by observing a rectangular area measuring 10 mm vertically and 10 mm horizontally on the surface of the transparent substrate sheet layer (1A) opposite to the injection-molded resin layer (2) with a microscope at 20x magnification, 50 to 80 of the coating fragments, each with a maximum length of 0.25 mm or less, can be identified.

4. A method for manufacturing an in-mold molded article, which produces an in-mold molded article according to any one of claims 1 to 3, A sheet installation step involves placing a transparent biaxially oriented polyolefin sheet (1a) with a thickness of 60 μm or more inside the cavity of the mold, The process includes a molding step of injecting and molding a resin material containing recycled plastic (2a) which includes coating fragments derived from the surface coating of waste plastic into the cavity, A method for manufacturing an in-mold molded product, comprising the molding step of injecting the resin material into the cavity so that it flows in a direction along the sheet surface of the biaxially oriented polyolefin sheet (1a).

5. The method for manufacturing an in-mold molded article according to claim 4, wherein the biaxially oriented polyolefin sheet (1a) has a degree of crystallinity of 70% or more due to X-ray diffraction when irradiated with X-rays from the cut surface.

Citation Information

Patent Citations

  • Fiber treatment agent

    JP1989014378A